The PEOPLE OF GOD: SCRIPTURE, RACE AND IDENTITY IN AFRICAN PERSPECTIVE - Dovlo, Elom (Ghana journal of religion and theology, 2017)
This paper reviews how Africans in the Diaspora and in Ghana have interpreted race and identity within the context of scripture. It discusses some of the influences of African Diasporic religious movements on Ghanaian biblical identity construction. But the main aim is to probe, using Ghana as our example, how continental Africans have constructed positive identities from scripture in the face of the question of race. The deliberate choice of Ghana is to use a familiar context which is different from the extremely suppressive history of the Americas and Apartheid southern Africa, yet has long history of religious exchange with the African Diaspora